Application of the Fuzzy Mamdani Method to Predict the Number of Customers Based on the Weather and Holidays in a Simple Restaurant on Abdul Hakim Street - Gultom, Parapat; Thianujaya, Wendy Thianujaya; Sirait, Annisa Hidayati; Kristian, Abel (Journal of Research in Mathematics Trends and Technology, 2024)
This research aims to optimize marketing strategies in the food industry by applying the Fuzzy Mamdani method. This approach considers factors such as the number of customers, weather conditions, and holidays to forecast the number of customers who will come to a simple restaurant. By using the Fuzzy Mamdani model, this research seeks to generate more effective marketing strategies by taking into account variability in consumer behavior. The results of this research are expected to help food business owners to optimize their raw material inventory more precisely, so as to improve operational efficiency and increase customer satisfaction.